Work fragmentation in developer interaction data. Issue 3 (30th January 2017) - Cruz, Luis C.; Sanchez, Heider; González, Víctor M.; Robbes, Romain
ABSTRACT: Information workers and software developers are exposed to work fragmentation, an interleaving of activities and interruptions during their normal work day. Small‐scale observational studies have shown that this can be detrimental to their work. In this paper, we perform a large‐scale study of this phenomenon for the particular case of software developers performing software evolution tasks. Our study is based on several thousands interaction traces collected by Mylyn and the Eclipse Usage Data Collector. We observe that work fragmentation is correlated to lower observed productivity at both the macro level (for entire sessions) and at the micro level (around markers of work fragmentation); further, longer activity switches seem to strengthen the effect, and different activities seem to be affected differently. These observations give ground for subsequent studies investigating the phenomenon of work fragmentation.